Biofixation of CO₂ emissions from natural gas combined cycle power plant - Gisela M. Oliveira; Nídia Caetano; Teresa M. Mata; António A. Martins (Energy Reports, 2020)
The growing impacts of climate change mainly due to the increasing emissions of GHG, especially carbon dioxide, has led to the development and implementation of specific strategies and policies to reduce them. Carbon capture and utilization (CCU) is currently seen as a good option, as it contributes to reduce the net carbon emissions and fulfil the goals of the Paris Agreement. This work analyses the economic potential of CO2 biofixation by microalgae from the exhaust gas of a Portuguese Natural Gas Combined Cycle (NGCC) power plant. Literature and real operational data are used, collected from reports of Portuguese power generation companies. A preliminary design and economic analysis of the carbon biofixation system was done. Results show that, although requiring a very large investment, the process is economically viable. In further studies a more in depth approach and detailed project combined with a sensitivity analysis, and a comparison with the chemical based CO2 fixation will be done.
Keywords: 330; Biological fixation; CO emissions; Microalgae; Natural gas combined cycle power plant